Heterogeneous subpopulations in Escherichia coli strains acquire adaptive resistance to imipenem treatment through rapid transcriptional regulation - Luo, YunTao; Xu, Rong; Yuan, Bo; Yang, WeiHua; Zhou, YunHeng; Tian, Yuan; Wang, QingZhong (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionHeteroresistance is a well-known phenomenon contributing to treatment failure in bacterial infections. Previous research has traditionally linked it to genetic mechanisms, emphasizing fixed subpopulations with specific resistance mutations. Recent studies appreciated that bacterial subpopulations may not be fixed and independent, but rather dynamically changing. Heteroresistance mechanisms are likely more intricate than mere genetic predisposition alone.MethodsOur study investigated the role of non-genetically encoded mechanisms in early stages of occurrence and development of heteroresistance through transcriptome analysis and molecular biology experiments.ResultsWe identified a clinical Escherichia coli strain that, despite no prior antibiotic treatment, still exhibited imipenem heteroresistance. We found that these heteroresistance populations can rapidly acquire adaptive capability for imipenem-resistance through an active and dynamic gene regulatory process. At their highly resistant stage, the transcriptome is primarily characterized by enhanced expression of related genes in exopolysaccharide and peptidoglycan biosynthesis (wcaE, wcaF, mrcB, murA, etc), leading to critical alterations in bacterial intracellular and intercellular structure, including maintaining the integrity of the outer cell membrane and the promotion of biofilm formation. Conversely, in antibiotics-free conditions, these highly imipenem-resistant subpopulations can revert to an imipenem-sensitive state, accompanied by reversed gene expression. Additionally, we discovered that extremely low-level antibiotic exposure can regenerate heteroresistance populations, accompanied by similar pattern of gene expression.DiscussionOverall, our study revealed non-genetic mechanisms that enable bacterial strains to acquire adaptive imipenem-resistance rapidly. Moreover, preventing hospital-acquired infections should focus not only on eliminating residual bacteria but also on removing residual antibiotics in clinical settings.